Managing human behavior in public & nonprofit organizations - Denhardt, Robert B.; Denhardt, Janet Vinzant; Aristigueta, Maria Pilar, 1956- (Thousand Oaks, Calif. : Sage, 2002)
This book covers all of the essential topics in management and organizational behaviour from the perspective of public and non profit management. It focuses on the importance of understanding the behaviour, motivations, and actions of individuals in the public service and the distinctiveness of management and leadership in public organizations. It contains cases studies, self-assessment exercises, simulations, and evaluative instruments. This book will assist all public managers to develop the skills and understanding they need in order to be effective and responsible.
Organizational Behavior As A Way Of Thinking And Acting -- The Roots of Organizational Behavior -- Some Early History -- Values and Assumptions of Organizational Behavior -- Knowing And Managing Yourself -- Life Experiences -- Your Lifeline -- Improving Your Sense of Self -- The Power of Vision -- Assessing Yourself -- Increasing Self-Knowledge -- A Vision Statement -- Laura's Dilemma -- Fostering Creativity -- Characteristics of Creative Individuals -- Conceptual Skills and Abilities -- Creativity as Behavior -- Creativity as a Process -- An Integrated Perspective on Creativity -- Why Do We Need Creativity in Public Organizations? -- The Creative Process -- Roles in the Creative Process -- Impediments to Creativity -- Defining the Problem Incorrectly -- Judging Ideas too Quickly -- Stopping at the First Acceptable Idea -- Lack of Support -- Other Ways of Thwarting Creativity -- Fostering Creativity in Organizations -- Challenging Work -- Supportive Supervision -- Organizational and Work Group Culture -- Workload Pressures and Resources -- Fostering Creativity--Putting It All Together -- Techniques for Improving Creativity -- The Idea Box or Matrix Analysis -- Synectics -- Enhancing Your Personal Creativity -- Using Analogies -- A Creativity Challenge -- Managing Stress -- Symptoms of Stress -- Stress Inventory -- Sources of Stress -- Coping With Stress -- The Consequences and Costs of Stress -- Stress: Good, Bad, and Ugly -- Sources of Stress on the Job -- Interpersonal Relationships -- Role Ambiguity and Conflict.
Includes bibliographical references and index.
Keywords: Public administration; Nonprofit organizations -- Management; Organizational behavior; Administration publique (Science); Associations sans but lucratif -- Gestion; Comportement organisationnel